Discussing the teaching of composition at the university - Behr, Yuri; Mamedes, Clayton Rosa; Chueke, Isaac Felix (Revista Vórtex, 2020)
The challenge involved in the teaching of musical composition is somewhat analogous to the issue of reconciling theory and practice; this is when the teacher– student relationship triggers a flow of information that leads to the construction of new concepts that are established by either or both sides. The present paper emerged from a roundtable held at the “The Teaching of Composition at the University” colloquium, which took place at the State University of Paraná in November 2019. The authors did not attempt to arrive at definitive conclusions but, rather, point out directions for critical reflection and practical approaches about the issue of teaching composition. The occasion was also an excellent one for sharing didactic experiences taking place at universities in Brazil and abroad.